Observing Archives: Web Archiving as Socio-Technical Practice - Ogden, Jessica; Halford, Susan; Carr, Leslie (AoIR Selected Papers of Internet Research, 2017)
This paper presents the preliminary results of an ethnographic study of web archiving, in an effort to explore the ways in which practitioners shape the preservation and maintenance of the archived Web in its various forms. A combination of non/participant observation, documentary sources and interviews were conducted over the course of several weeks in collaboration with web archivists, engineers and managers at the Internet Archive – a private, non-profit digital library that has been archiving the Web since 1996. Whilst several socio-technical components of practice have been identified thus far, this paper focuses on the types of ‘knowledge work’ that informs the selection, collection, repair and maintenance of the archived Web(s). This work draws on Downey (2014) and recent calls within STS (Jackson 2014; Russell & Vinsel 2016) to move beyond a pre-occupation with innovation to consider the repair and maintenance of technologies as potential sites of critical engagement and social discourse. Here the concept of ‘web archival labour’ is proposed to encompass these practices and highlight the ways in which web archivists (as both networked human and non-human agents) shape and maintain the preserved Web through practices that are often embedded in and obscured by the complex technical arrangements of collection and access. As a result, this engagement positions web archives as places of knowledge and cultural production in their own right, revealing new insights into the performative nature of web archiving that have implications for how these new forms of social data are used and understood.